The Expereince of Music Performance Anxiety Among Greek Female Singers./A Phenomenological Interpretative Analysis. - Altanopoulos Fillipos; Louka Penelope (2016)
Introduction, Methods, Design, Participants, Data Collection, Data Analysis, Analysis, Discussion, Reflexivity, References.